Cambios en la vía aérea después de cirugía ortognática bimaxilar en pacientes con maloclusión clase III esquelética (2008)
ABSTRACT: Orthognathic surgery is a treatment alternative for patients with maxillary mandibular skeletal discrepancies. In this procedure hard and soft tissues of the craniofacial complex are modified, this includes the airway. The purpose of this study is to present a descriptive analysis of cephalometric changes in the airway of twenty patients, eleven females nine males, subjected to bimaxillary orthognathic surgery, (maxillary advance – mandibular retrusion at the Hospital Universitario San Vicente de Paúl), Medellín, Colombia. Methods: three lateral cephalometrics head plates were taken, scanned and digitalized in each patient, and the airway measurements were compared before, at eight and eighteen months after surgery. Results and Conclusions: significant increases in the upper pharyngeal space were found in the area of oro pharynx after surgery. The area of the lower pharyngeal space and the hypo pharynx did not show significant increases. Significant changes were found in the position of the hyoid bone between males and females. Bimaxillary orthognathic surgery increased the dimensions of the upper airway. These changes were determined by the type of surgical procedure (Le Fort I maxillary advancement osteotomy and mandibular retrusion) and by the magnitude of the movement performed in the maxilla and the mandible. Also, modification in the position of structures such as the soft palate, the hyoid bone and the tongue, were observed.